Worth the Effort? Rehabilitation Causes and Outcomes and the Assessment of Post-Release Survival for Urban Wild Bird Admissions in a European Metropolis - Marc Engler; Rebekka Sens; Maja Lundberg; Alexandra Delor; Marco Stelter; Malte Tschertner; Sina Feyer; Stephanie Zein; Lesley Halter-Gölkel; Rainer Altenkamp; Kerstin Müller (Animals, 2025)
Globally, millions of wild birds are admitted to rehabilitation centres each year. We analysed data on wild bird admissions at an urban rehabilitation centre in Berlin, Germany, collected over 20 years (2005–2024), aiming to (a) characterise admission causes and demographics, (b) investigate the rehabilitation duration and release probability across admission causes and systematic bird groups, and (c) assess post-release survival as a proxy for rehabilitation success. Longer rehabilitation durations were generally associated with orphaned birds and those in poor condition or who had had an infection. Orphans and birds with undetermined admission causes were most likely to be released. Birds that were admitted in poor condition were least likely to be released, which was particularly the case among Passerines. The monitoring of post-release survival through ring recovery data revealed higher recovery rates for larger birds but no informative value on post-release survival across species; thus, it did not represent an ideal measure of rehabilitation success in terms of the original objective. We conclude that the extent, outcome, and success of wild bird rehabilitation may depend on the initial cause of admission and may differ between bird groups. Advanced measures to assess post-release survival should be considered to allocate the limited resources and the conservation efforts of wild bird rehabilitation centres to birds of species and/or admission causes best suited to undergoing rehabilitation.